Penerapan Metode Secure Software Development Life Cycle pada Website Usaha Mikro Kecil dan Menengah “Sultan Kreatif” - Pane, Hadit Billa Darma; Kasmawi, Kasmawi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Analyze and apply the System Development Life Cycle method in websiten development for Sultan Kreatif Micro, Small, and Medium Enterprises. With the increasing need for digitalization among MSMEs, the application of the method is expected to improve the process of developing an efficient and effective website. The research method used is qualitative with a case study approach. The results of the study show that the application of the method not only helps in producing a functional and user-friendly website, but also provides clear guidance for developers at every stage. With a good website, it is hoped that Sultan Kreatif MSMEs can increase their visibility and competitiveness in the digital market. This research is expected to be a reference forthe development of other MSME websites